Excitons in monolayer transition metal dichalcogenides. (20th July 2015) - Li, J; Zhong, Y L; Zhang, Dong
Abstract: We theoretically investigate the exciton formed with two massive Dirac particles in monolayer and other transition metal dichalcogenides as well as two layers separated by a dielectric layer. In the low-energy limit, the separation of the center-of-mass and relative motions is obtained. Analytical solutions for the exciton wave function and energy dispersion are obtained including the Coulomb interaction between electron and hole, the exciton Bohr radius, binding energy and its effective mass are obtained in monolayer transition metal dichalcogenides. In the case of two monolayers separated by a dielectric layer, we find that the exciton effective mass can be continuously tuned by the interlayer separation.